Development of a soot radiation model for diesel flames. (5th July 2019) - López, José J.; García-Oliver, José M.; García, Antonio; Villalta, David
Highlights: Radiation model is based on two sub-models: spray model and soot model. The spray model estimates a penetration very similar to the experimental values. Soot Yield concept combines the soot formation and oxidation processes. Higher radiant fraction value is obtained when the oxygen molar fraction is reduced. The radiant fraction shows values from 0.11% to 0.43% respect to the total fuel energy. Abstract: This paper describes a radiation model for diesel sprays that can predict the heat losses based on spray characteristics to the spray plume due to radiation. The model is based on three sub-models: spray model, soot model and radiation model. The spray model is a one-dimensional model that simulates the axial and radial distribution of a fuel spray for each instant. The soot model is a one-dimensional tool, which is based on formation and oxidation processes calculating the axial and radial soot concentration profile for each instant. The output results of the two sub-models are used as input information for the radiation model, which obtains the radiation heat transfer values for a diesel flame. The experimental measurements used to adjust the different constants and to validate the sub-models were performed in a high-pressure high-temperature vessel using three different optical techniques: Schlieren, to obtain spray penetration, Diffused Back-Illumination technique (DBI) for the soot concentration and the 2-color method for calculating the soot temperature and concentration. The radiant fraction shows values from 0.11% to 0.43% with respect to the total energy of the fuel depending on the operating condition. Taking into account the different assumptions taken for modeling the spray radiation, these results are consistent with those obtained in the literature, in which the radiation was characterized under similar conditions.